(1005) Health Services Marketing: The Case of family Planning جدوى تطبيق تقنيات التسويق : دراسة حالةعلى برامج تنظيم الأسرة - R. Sh. Bessada. (INP., 2020)
This paper examines the feasibility of applying marketing techniques to family planning programs, addressing both the opportunities and challenges involved. While some researchers support the integration of marketing into health services, others remain skeptical. However, just as scientific advancements have proven once-unthinkable feats possible—such as space exploration— as there is potential for marketing to enhance public health initiatives. By developing tailored marketing strategies that align with the unique needs of family planning services.